2010
DOI: 10.1177/1527154410386802
|View full text |Cite
|
Sign up to set email alerts
|

Configurative Domains in Child Health Research: Sudden Infant Death in the Swedish Medical Journal

Abstract: The aim of present investigation is to discover publishing portrayals embedded in sudden infant death informatics disseminated by a medical journal at regional level. In particular, gender configurative domains regarding health policy and nursing practices are scrutinized. A qualitative literature review was performed using a critical discourse analytical approach. The full texts of 55 articles/comments published within the field by the Swedish Medical Journal from January 1, 1980 to March 6, 2007 were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…It might seem surprising that the theoretical and methodological discourse analytical approach outlined by Foucault (1972/82) is used in the present survey, as Foucault has been criticized for taking the masculine world as an entry-point for gendered observations (see the discussion regarding this in Connell, 2002). However, the author´s justification through earlier studies (Brännström, 2010a;Brännström, 2010b) for using a critical discourse-analysis framework, as outlined by Foucault, is that his theoretical and methodological approach-by discovering text domains in knowledge production-is well suited to the illumination of knowledge production in medical science i.e., principal text portraits/domains in medicine (see, e.g., Foucault, 1972/82, Chapters 1 and 6).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It might seem surprising that the theoretical and methodological discourse analytical approach outlined by Foucault (1972/82) is used in the present survey, as Foucault has been criticized for taking the masculine world as an entry-point for gendered observations (see the discussion regarding this in Connell, 2002). However, the author´s justification through earlier studies (Brännström, 2010a;Brännström, 2010b) for using a critical discourse-analysis framework, as outlined by Foucault, is that his theoretical and methodological approach-by discovering text domains in knowledge production-is well suited to the illumination of knowledge production in medical science i.e., principal text portraits/domains in medicine (see, e.g., Foucault, 1972/82, Chapters 1 and 6).…”
Section: Discussionmentioning
confidence: 88%
“…McLaren (2002) and Connell (2002) also remind the reader that there is no consensus among feminist theorists regarding Foucault´s approach, although they do note that Foucault has been criticized for stereotyping gender processes. However, in previous studies the author found a critical discourse analysis methodology, as outlined by Foucault (1972/82), to be a valuable tool when searching for meanings within a text, for example, when the intention is to discover publishing domains, including power processes, surrounding gender recognition in scientific knowledge production (Brännström, 2010a;Brännström, 2010b). Context, as used in the present study, includes the physical study environments targeted by the abstracts (e.g., child health clinics, neonatal nursing wards, or school health clinics etc.…”
Section: Critical Discourse Analysismentioning
confidence: 98%
“…However, very few studies have focused on the publishing portraits revealed within current research concerning sudden death in infancy (Brännström ). Thus, the present survey emanates from investigations regarding discursive domains identified within key references (original articles) on SIDS disseminated internationally (Brännström ) and in Sweden (Brännström ), respectively. The results from these two surveys showed that preventive and parenting recommendations, despite coming partly from different geographical regions, were transmitted with limited or no clear recognition of social and economic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The results from these two surveys showed that preventive and parenting recommendations, despite coming partly from different geographical regions, were transmitted with limited or no clear recognition of social and economic contexts. The gendered publishing portrayals observed in the Swedish material revealed that men as individual fathers/caregivers were almost invisible but had the principal say in the public space (as authors), while women made extensive appearances in the private space (as mothers) but were marginalised or questioned as professional authors in this field of medicine (Brännström ). The intention in the current survey is therefore to go further and scrutinise the observed male‐dominated scientific coverage of SIDS, by means of a more in‐depth deconstruction of the gendered portraits, visible in the published portrayals of women/mothers as revealed in a journal of medicine at national level in a northern European country viz.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation